Effiziente MHz-Wechselrichter mit unipolaren SiC-Transistoren für Hochleistungs-Induktionslampen - Hähre, Karsten (KIT Scientific Publishing, 2016)
This work presents the design and investigation of a novel UV-lamp-system, which is based upon UV-induction lamps and a MHz-inverter equipped with normally-on junction field effect transistors (JFET). A system efficiency of some more than 27 % is verified with the prototype UV-induction lamp system, which positions between the two previous UV-systems and open up new fields of application.